The Effect of 5S on Employee Performance: An Empirical Study among Lebanese Hospitals - Rayan Ezzeddine; Malak Aoun (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2020)
When studying the regular quality practices in hospitals, it is essential to focus on the 5S as it reflects the daily activities of healthcare providers. The aim of this research is to study the effect of 5S-quality approach on employee performance in some Lebanese hospitals. Based on a quantitative approach, a survey was conducted among four hospitals in South Lebanon and 240 self-administered questionnaires were distributed randomly among target respondents. The collected primary data was analyzed by SPSS software. Statistical tests were applied for hypothesis testing such as correlation and regression analysis tests. The obtained results showed that 5S is significantly and positively affecting employee performance except for Sort. This study was limited to the constricted geographical zone and small number of hospitals was surveyed. Future studies may enlarge the research empirically and study different quality approaches.